2005
DOI: 10.1007/s00280-005-0063-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of irofulven cytotoxicity in combination with cisplatin and oxaliplatin in human colon, breast, and ovarian cancer cells

Abstract: Irofulven displays synergistic antiproliferative and pro-apoptotic effects when combined with oxaliplatin over a broad range of concentrations in human colon and breast cancer cells. Acquired resistance to irofulven has limited impact on the effects of cisplatin-irofulven and oxaliplatin-irofulven combinations. Based on these data, irofulven-oxaliplatin and cisplatin-irofulven combinations will be further explored in clinical trials, favoring the use schedules of oxaliplatin given prior to irofulven in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
1
28
0
1
Order By: Relevance
“…Previous studies conducted in tumor cell lines with wild-type or mutant p53 suggested that the cytotoxicity induced by irofulven is independent of p53 status [55][56][57]. In this study, the chemosensitivity to irofulven was compared in isogenic HCT116 p53+/+ and p53−/− cells.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies conducted in tumor cell lines with wild-type or mutant p53 suggested that the cytotoxicity induced by irofulven is independent of p53 status [55][56][57]. In this study, the chemosensitivity to irofulven was compared in isogenic HCT116 p53+/+ and p53−/− cells.…”
Section: Discussionmentioning
confidence: 98%
“…The IR spectrum showed absorption at 3439 cm −1 due to the hydroxy groups. 13 C NMR data analysis suggested that 2 was also an illudin-type sesquiterpenoid as deduced from the characteristic signals at δ C 26.6 (s, C-3), 14.9 (t, C-11), and 10.0 (t, C-12) for the three-membered carbon ring and the quaternary resonance at δ C 38.2 (s, C-7). 2D NMR data analysis indicated that compound 2 was structurally resembled illudane, 16 except for the terminal double bond between C-2 and C-10 becoming saturated in 2, as supported by the HMBC correlation of δ H 0.97 (3H, d, J = 6.8 Hz, H-10) with δ C 46.8 (d, C-2), 75.8 (d, C-1), and 26.6 (s, C-3).…”
Section: Resultsmentioning
confidence: 99%
“…In the 13 C NMR data, three characteristic signals at δ C 27.6 (s, C-3), 5.3 (t, C-11), and 6.4 (t, C-12) revealed the existence of a three-membered carbon skeleton (ring A). 8,9 These information, along with the characteristic quaternary carbon resonance at δ C 37.8 (s, C-7) and four methyl groups (including two oxidated ones) led to the hypothesis that compound 1 might be an illudin-type sesquiterpenoid possessing a 3/6/5 carbon skeleton (rings A-C as shown in Figure 1) as those reported previously from the same resource.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various combination regimens have become a major strategy for overcoming drug resistance and improving response and cure rates (34)(35)(36), and these should be able to decrease the adverse effects of the drugs. Therefore, drug interactions may be fully recognized when TAO + cisplatin combination chemotherapy is administered to patients with advanced cervical cancer.…”
Section: Discussionmentioning
confidence: 99%